Action-based user authentication. (27th October 2008) - Yampolskiy, Roman V.
Network security partially depends on reliable user authentication; unfortunately currently used passwords are not completely secure. One of the main problems with passwords is that very good passwords are hard remember and the ones which are easy to remember are too short or simple be secure. We have designed a number of authentication schemas, which are easy to remember and can be relatively quickly provided to the system, while the same time remaining impossible to break with brute force alone. In this article, we have compared the size of password spaces and how easy they are remember for many popular alphanumeric and graphical authentication schemas against the approaches developed by us, namely PassText, PassArt and PassMap.